Are Auditory Steady-State Responses Useful to Evaluate Severe-to-Profound Hearing Loss in Children?. (18th October 2015) - Grasel, Signe Schuster; Almeida, Edigar Rezende de; Beck, Roberto Miquelino de Oliveira; Goffi-Gomez, Maria Valéria Schmidt; Ramos, Henrique Faria; Rossi, Amanda Costa; Koji Tsuji, Robinson; Bento, Ricardo Ferreira; de Brito, Rubens
Abstract : Objective . To evaluate Auditory Steady-State Responses (ASSR) at high intensities in pediatric cochlear implant candidates and to compare the results to behavioral tests responses. Methods . This prospective study evaluated 42 children with suspected severe-to-profound hearing loss, aged from 3 to 72 months. All had absent ABR and OAE responses. ASSR were evoked using binaural single frequency stimuli at 110 dB HL with a 10 dB down-seeking procedure. ASSR and behavioral test results were compared. Results . Forty-two subjects completed both ASSR and behavioral evaluation. Eleven children (26.2%) had bilateral responses. Four (9.5%) showed unilateral responses in at least two frequencies, all confirmed by behavioral results. Overall 61 ASSR responses were obtained, most (37.7%) in 500 Hz. Mean thresholds were between 101.3 and 104.2 dB HL. Among 27 subjects with absent ASSR, fifteen had no behavioral responses. Seven subjects showed behavioral responses with absent ASSR responses. No spurious ASSR responses were observed at 100 or 110 dB HL. Conclusion . ASSR is a valuable tool to detect residual hearing. No false-positive ASSR results were observed among 42 children, but in seven cases with absent ASSR, the test underestimated residual hearing as compared to the behavioral responses.